EPA and DHA can modulate cell death via inhibition of the Fas/tBid-mediated signaling pathway with ISKNV infection in grouper fin cell line (GF-1) cells. Issue 97 (February 2020) - Chen, Kuang-Wen; Chiu, Hsuan-Wen; Chiu, Yu-Wei; Wu, Jen-Leih; Hong, Jiann-Ruey
Abstract: Polyunsaturated fatty acids (PUFAs) play important roles in organisms, including the structure and liquidity of cell membranes, anti-oxidation and anti-inflammation. Very little has been done in terms of the effect of PUFAs on cell death, especially on DNA virus. In this study, we demonstrated that the infectious spleen and kidney necrosis virus (ISKNV) can induce host cell death via the apoptotic cell death pathway, which correlated to modulation by PUFAs in grouper fin cell line (GF-1) cells. We screened the PUFAs, including docosahexaenoic acid (DHA) and eicosapentaenoic acid (EPA), for the ability of different dosages to prevent cell death in GF-1 cells with ISKNV infection. In the results, each 10 μM of DHA and EPA treatment enhanced host cell viability up to 80% at day 5 post-infection. Then, in Terminal deoxynucleotidyl transferase (TdT) dUTP Nick-End Labeling (TUNEL) assay, DHA- and EPA-treated groups reduced TUNEL positive signals 50% in GF-1 cells with ISKNV infection. Then, through studies of the mechanism of cell death, we found that ISKNV can induce both the Bax/caspase-3 and Fas/caspase-8/tBid death signaling pathways in GF-1 cells, especially at day 5 post-infection. Furthermore, we found that DHA and EPA treatment can either prevent caspase-3 activation on 17-kDa form cleavage or Bid cleaved (15-kDa form) for activation by caspase-8, apparently. On the other hand, the anti-apoptotic gene Bcl-2 was upregulated 0.3-fold and 0.15-fold at day 3 and day 5, respectively, compared to ISKNV-infected and DHA-treated cells; that this did not happen in the EPA-treated group showed that different PUFAs trigger different signals. Finally, ISKNV-infected GF-1 cells treated with either DHA or EPA showed a 5-fold difference in viral titer at day 5. Taken together, these results suggest that optimal PUFA treatment can affect cell death signaling through both the intrinsic and extrinsic death pathways, reducing viral expression and viral titer in GF-1 cells. This finding may provide insight in DNA virus infection and control. Graphical abstract: Image 1 Highlights: Iridovirus (ISKNV) infection can induce Fas-mediated and Bax-mediated cell death signaling in GF-1 cells. Polyunsaturated fatty acids (PUFAs) play important roles in organisms, including the structure and anti-oxidation and anti-inflammation, but very few in cell death via viral infection. The PUFAs treatment also reduce host cell death via extrinsic death signals and mildly decrease viral titer with ISKNV infection.